Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Derivation of Pogson's law

  1. Feb 3, 2012 #1
    Hello i am strugling to derive Pogson's law, i feel i am soo close, but i am not there yet. Here is what i ve done soo far.


    \begin{equation}
    \begin{split}
    j_6 \cdot 100 &= j_1\\
    \frac{j_6}{j_1} &= \frac{1}{100}\\
    \frac{j_6}{j_1} &= 10^{(-2)}\\
    \frac{j_6}{j_1} &= 10^{-0,4\cdot 5}\\
    \frac{j_6}{j_1} &= 10^{-0,4\cdot (m_6 - m_1)}\\
    \frac{j_1}{j_2} &= 10^{-0,4\cdot (m_1 - m_2) }\\
    \frac{j_1}{j_2} &= 10^{-0,4\cdot (m_1 - m_2) }\\
    \frac{j_1}{j_2} &= 2,5^{-(m_1 - m_2) }\\
    \log_{10} \frac{j_1}{j_2} &= \log_{10} 2,5^{-(m_1 - m_2) }\\
    \log_{10} \frac{j_1}{j_2} &= -(m_1 - m_2) \cdot \log_{10} 2,5\\
    (m_1 - m_2) &= -\frac{\log_{10} \frac{j_1}{j_2}}{\log_{10} 2,5}\\
    \end{split}
    \end{equation}

    What am i missing???
     
  2. jcsd
  3. Feb 3, 2012 #2
    I allready got it. TY
     
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook